Numerical analysis of wave mixing in 3‐D infinite elastic solids with a spherical damage. Issue 1 (25th January 2021) - Ankay, Benjamin; Zhang, Chuanzeng
Abstract: In this paper the 3‐D wave propagation in an infinite elastic solid with a spherical damage is numerically simulated by a mapped staggered Chebyshev pseudo‐spectral collocation method. In the numerical simulation process, the so‐called Convolutional‐Perfectly‐Matched‐Layers (CPML) are used to model the absorbing boundaries and the wave excitations are specified inside the corresponding physical domain. Furthermore, to consider different damage models the classical nonlinear elastic and non‐classical hysteretic material laws are used. The main objective of this study is to evaluate the influences of the particular wave modes and the mixing of the incident waves on the generated nonlinear scattered wave field. To analyze the specific scattered wave fields around the spherical damage region the computed time‐domain signals are transformed to the frequency‐domain.